Penerapan Sistem Pendukung Keputusan Pada Pengambilan Keputusan Penilaian Kinerja Karyawan dengan Menerapkan Metode MOOSRA - Utomo, Dito Putro (Journal of Computer System and Informatics (JoSYC), 2024)
The quality of the company will increase as employee performance increases. There are many ways that companies or organizations can improve employee performance. One way is to provide awards or rewards for employees who excel and for employees who are not able to provide their best performance, they will be given as a consequence. Rewards will be given by assessing employee performance. So far, Kofipindo has only relied on leaders' decisions to assess employee performance. This makes employees less motivated to show their best performance. Decision support systems are alternative solutions or alternative means and steps to resolve problems so that problems can be resolved effectively and efficiently. The Moosra method is used to calculate the weight of the criteria and determine the level of rejection as the main criterion. Where the decision support system is used as a model or reference in the decision-making process, especially in the employee performance assessment process. The Moosra method examines the suitability of separating a set of alternative value data with certain criteria described in the decision matrix. The aim of the research is to assist in the employee performance assessment process, making it easier for companies to provide rewards for the performance results of selected employees. The results obtained in the research process were Alternative (A10) with the name Roland Zebua as the employee with the best performance assessment.